Teaching Dante - Metress, Christopher (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In October 2018, Samford University hosted Teaching Dante, a conference designed to help non-specialists teach the work of the Florentine poet more effectively in undergraduate core and general education courses. This volume of essays on the Divine Comedy includes a keynote address by Albert Russell Ascoli (UC-Berkeley), as well as a selection of top papers from the conference